Libya : Technical Assistance Report-Public Financial Management Reform Priorities in the New Environment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2013)
Libya faces a number of challenges to establishing a robust, efficient, and transparent public financial management system. There is a need to establish a clear macrofiscal policy framework. The Sovereign Wealth Fund (SWF) should be a financing fund system with clear and rigid inflow and outflow rules and should be based on clear and regulated investment criteria. Under the existing legal and regulatory framework, budget expenditures cannot exceed the initial ceilings specified in the annual budget law. This should be strictly enforced.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet